Development of an effective method utilizing fibrin glue to repair pleural defects in an ex-vivo pig model - Nobuyuki Kondo; Yoshitaka Takegawa; Masaki Hashimoto; Seiji Matsumoto; Shiro Oka; Seiki Hasegawa (Journal of Cardiothoracic Surgery, 2020)
Abstract Background The present study aimed to use an ex-vivo model to investigate whether a new method involving the use of fibrin glue and a polyglycolic acid (PGA) sheet under ventilation enhances the sealing effect after repair of the pleural defect. Methods Ex-vivo pig lungs were used in this study. We investigated the maximum pressure tolerance of pleural defects repaired using three methods: 1, directly spraying fibrin glue over a PGA sheet; 2, spreading fibrinogen on the site then sealing with a PGA sheet and spraying with fibrin glue; and 3, spreading fibrinogen while maintaining ventilation then sealing with a PGA sheet and spraying with fibrin glue. Results The maximum tolerable pressures were as follows (mean ± standard deviation, cmH2O): Method 1, 37.1 ± 13.6, Method 2, 71.4 ± 27.7, Method 3, 111.5 ± 8.8. Histological findings explained the difference in tolerable pressure at the repaired site between methods. Microscopic findings of lungs repaired using Method 3 indicated that the fibrinogen penetrated into deeper tissues to act as an anchor. Conclusions Fibrin glue sealing under ventilation increases the anchoring effect of repairing air leakages due to pleural defect in an ex-vivo model. This method may have clinical application. For example, it may be useful to reduce severe air leakage in patients who undergo lung-sparing surgery for a pleural tumor.